Football society players over the age of 55: how stressful can a match be? - José Luiz Lopes Vieira; Fredi Telles da Silva; Vânia de Fátima Matias Souza; Adolpho Amorim; Luciana Ferreira (Universidade Estadual de Maringá, 2021)
This study aimed at assessing the physical activity level, heart rate and the salivary cortisol level of football society players. The sample consisted of 19 male masters football players with an average age of 56.7 ± 3.9 years. The long form of the International Physical Activity Questionnaire (IPAQ) and Polar® heart rate monitors were used as instruments, in addition to Salivette® tubes to measure salivary cortisol. Data analysis was performed by using the repeated measures Analysis of Variance (ANOVA) with Bonferroni post hoc test, and Spearman's Rank Correlation Coefficient. The results showed that the salivary cortisol concentration indicated an index of 1.97 ng/ml at the beginning of the match; 40 minutes after that these values increased to 8.00 ng/ml, and 60 minutes after the match had started they reached 8.40 ng/ml. Considering the post-match moment, a moderate and positive correlation between the salivary cortisol concentration and heart rate (average and maximum) was seen. In conclusion, the physical effort expended during football Society practice needs to be monitored due to the high heart rate and high increase in the salivary cortisol concentration of this age group.